Science World [motion pictures] Chemistry : periodic table and periodicity; - reaction rates and equilibrium. - Coronet (Northbrook, IL Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol. 24: Periodic table and periodicity; - Reaction rates and equilibrium
Original copy in VHS format (VHS 24)
[Distributed by] International Book Center, Philippines
Keywords: Cycles; Chemical Equilibrium